Perception of Post Graduate Accounting Students on Semar Spiritual Philosophy in Building Accounting Knowledge - Prasetyo, Whedy (Jurnal Akuntansi Multiparadigma, 2012)
Abstract: Perception of Post Graduate Accounting Students on Semar Spiritual Philosophy in Building Accounting Knowledge. The study explains the description of and the meaning attribution to spiritual philosophy of Semar character from wayang, as perceived by students of post graduate program of accounting, Brawijaya University. The existence of spiritual characterization of Semar will provide spiritual value that transforms accounting into knowledge in which God is perceived as base of soul. Consequently, accountants will generate value of truthfulness in accounting analysis and can reduce the corrupting practice and violation to reach the value serenity of fi nancial report that shows values such as honest, responsible, discipline, fast and accurate, fairness, visionary, empathy and gratitude. Abstrak: Persepsi Mahasiswa Pasca Sarjana Akuntansi tentang Filosofi Spiritual Semar dalam Membangun Ilmu Akuntansi. Studi ini menjelaskan pemahaman dan pemaknaan atas fi losofi spiritual Semar dari karakter wayang sebagaimana dipersepsikan oleh mahasiswa pasca sarjana akuntansi Universitas Brawijaya. Keberadaan eksistensi karakterisasi Semar akan menyediakan nilai spiritual yang dapat mentransformasi akuntansi menjadi pengetahuan di mana Tuhan menjadi landasannya. Sebagai konsekuensi, akuntan akan menghasilkan analisis akuntansi yang memiliki nilai kebenaran, serta mengurangi praktik korupsi, untuk mencapai kedamaian dalam laporan keuangan yang menunjukkan nilai-nilai seperti kejujuran, tanggung jawab, disiplin, kecepatan dan keakuratan, kewajaran, memiliki visi, empati dan syukur.